The Trouble with KISSing and Other Mnemonic Devices - Graybeal, Christy Danko; Strickland, Tricia K. (Ohio Journal of School Mathematics, 2018)
In this article, the authors share research on the use of mnemonic devices in mathematics in- struction. In particular, they address the following questions: What are mnemonic devices? What are their benefits? What should teachers be cautious about? How should mnemonic devices be used?